1990
DOI: 10.1136/gut.31.12.1355
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal intraluminal pH in normal subjects and those with colorectal adenoma or carcinoma.

Abstract: Recent evidence suggests that the production of colorectal carcinogens is facilitated when the pH of the colonic contents is alkaline. It follows that the colonic intraluminal pH of patients with colorectal neoplasms should be higher than in normal subjects. Gastrointestinal pH has been measured in 30 patients with colorectal cancer and 37 patients with benign colorectal adenomas (using a pH sensitive radiotelemetry capsule). These values have been compared with those recorded in 66 normal subjects. No differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…The median pH value was 6.2. This is in agreement with median fasting duodenal pH values reported in the literature, which vary from 5.95 to 6.72 (10Y13, 15,50,51). pH of duodenal aspirates drifted to higher values, increasing by up to 6% within 20 min at room temperature.…”
Section: Fasted Duodenumsupporting
confidence: 93%
“…The median pH value was 6.2. This is in agreement with median fasting duodenal pH values reported in the literature, which vary from 5.95 to 6.72 (10Y13, 15,50,51). pH of duodenal aspirates drifted to higher values, increasing by up to 6% within 20 min at room temperature.…”
Section: Fasted Duodenumsupporting
confidence: 93%
“…8 The reduction in pH associated with the production of SCFAs has been proposed as a protective factor5 as a higher faecal pH has been noted in high risk populations.20 Some studies have shown high faecal pH in persons with colonic cancer,2' although others have failed to confirm these findings. 22 We detected no differences in faecal pH in our three subject groups suggesting that neither the FAP gene nor the presence of polyps influences faecal pH.…”
Section: Discussionmentioning
confidence: 52%
“…The normal pH in the vagina is pH 4, but after the deposition of semen, it may reach pH 8. The normal rectal pH range in adult males is between pH 6 and 7 but has been shown to be as high as pH 8 (14,21,25,31). Ideally, a topical microbicide must thus retain its activity over a broad range of pH values.…”
Section: Discussionmentioning
confidence: 99%